2006
DOI: 10.1016/j.bandl.2005.06.007
|View full text |Cite
|
Sign up to set email alerts
|

EEG theta and gamma responses to semantic violations in online sentence processing

Abstract: We explore the nature of the oscillatory dynamics in the EEG of subjects reading sentences that contain a semantic violation. More specifically, we examine whether increases in theta ( approximately 3-7 Hz) and gamma (around 40 Hz) band power occur in response to sentences that were either semantically correct or contained a semantically incongruent word (semantic violation). ERP results indicated a classical N400 effect. A wavelet-based time-frequency analysis revealed a theta band power increase during an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
217
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 226 publications
(268 citation statements)
references
References 50 publications
41
217
10
Order By: Relevance
“…Delta (3-4 Hz) activity in our data localized to distributed lexico-semantic areas, suggesting that late slow, stimulus-locked oscillatory activity reflects higher stages of speech processing 36,37 and stabilizes sensory representations 38,39 . It is unclear how slow activity precisely relates to perception.…”
Section: Discussionmentioning
confidence: 64%
“…Delta (3-4 Hz) activity in our data localized to distributed lexico-semantic areas, suggesting that late slow, stimulus-locked oscillatory activity reflects higher stages of speech processing 36,37 and stabilizes sensory representations 38,39 . It is unclear how slow activity precisely relates to perception.…”
Section: Discussionmentioning
confidence: 64%
“…A speculative hypothesis then is that the DMN operates in theta mode (which is reflected in the scalp EEG by an increase in frontal theta) when it becomes less active (i.e., during engagement in a task). This would not only explain the observed BOLD decreases during engagement in a task Raichle et al, 2001), but it would also explain why frontal theta power has been shown to increase in a wide range of cognitive tasks, such as mental arithmetic Burgess and Gruzelier, 1997;Inanaga, 1998;Inouye et al, 1994;Iramina et al, 1996;Ishihara and Yoshii, 1972;Ishii et al, 1999;Lazarev, 1998;Mizuki et al, 1980;Sasaki et al, 1996;Smith et al, 1999), error detection tasks (Luu et al, 2003;Luu et al, 2004), language comprehension tasks (Bastiaansen et al, 2002;Hald et al, 2006) and working memory tasks (Gevins et al, 1997;Jensen and Tesche, 2002;Krause et al, 2000;Onton et al, 2005). However, although this suggestion would account for the observed pattern of theta power increases, it appears to contradict several previous functional interpretations that increased frontal theta oscillations reflect synchronous activity in brain regions that are involved in cognitively demanding tasks (Inanaga, 1998;Ishihara and Yoshii, 1972;Jensen and Tesche, 2002;Laukka et al, 1995;Onton et al, 2005;Smith et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, gamma power increases were observed in response to words that were semantically appropriate in a given sentence context, but not when the word induced a semantic violation in the sentence (Hald, Bastiaansen, & Hagoort, 2006),and when participants were presented with sentences in their native language, but not when they were presented with sentences in phonologically related or unrelated languages (Peña & Melloni, 2012). Finally, an increase in gamma power was observed when participants had successfully comprehended a degraded speech signal (Hannemann, Obleser, & Eulitz, 2007).…”
Section: Introductionmentioning
confidence: 90%